“DURMA” (Model Penciptaan Pesan dan Kesan Musik Melalui Pembenturan Teks Lirik dengan Ekpresi Musik) - Manggala, Bondan Aji (Institut Seni Indoensia Surakarta, 2020)
ABSTRACT This article is part of a report on the results of artistic research (works of music) in the field of music. Briefly expresses experience and some knowledge findings related to the process of creating musical works of art.